Factors Influencing Glycaemic Control in Older People with Type 2 Diabetes Mellitus on Oral Hypoglycaemic Therapy and Attending a Primary Health Care Centre in Negeri Sembilan, Malaysia - Ahmad, Akmal Naziah (2011)
The number of Malaysian citizen living above 60 years is currently about 7% of the total population. The prevalence of diabetes in Malaysia has increased from 8.3% (1996) to 11% in 2006. Non-pharmacological factors were reported to play an important role in the progression of the disease. Factors like physical inactivity, dietary pattern and lifestyle practices such as alcohol consumptions and smoking habit among type 2 elderly diabetics were the variables that were studied in relation to glycaemic control. The aim of this research is to determine the prevalence of glycaemic control and factors associated with poor glycaemic control among elderly type 2 diabetic patients attending a primary health care in Negeri Sembilan. Method: A cross-sectional study was conducted in July to October 2009 at a Primary Health Clinic in Port Dickson, Negeri Sembilan. A structured and pretested interviewer administered questionnaire was used for data collection. The respondents were type 2 diabetic patients 60 years and above of age. After screenings for inclusion and exclusion criteria, 230 respondents were selected in the study. Statistical Package for Social Science (SPSS) version 18 was used for data analysis. Results: The response rate was 78%. The results showed that the mean age was 68 ! 6 year and about 62% were less than 70 years. Majority of the respondents were female (5.5%), housewives (47.8%) and 60.4% have completed primary education. Sixty-one percent of the respondents had poor glycaemic control. A younger elderly (x2=6.701, p=0.010), living arrangement (x2=7.604, p=0.006), have non-home cook food (x2=3.869, p=0.049) and have dinner without companion (x2=7.642, p=0.006) show significant association. Additional to these, respondents on polytherapy (x2=21.593, p<0.001), duration of diagnosis 5 to 10 years (x2=5.958, p=0.050), age of first diagnosis less than 50 year (x2= 12.113, p=0.002) and uncontrolled serum triglyceride (Fishers exact test p=0.049) show significant association. Multiple logistic regression analysis resulted that Malay ethnicity (OR 2.5 95% CI 1.09-5.73), age of first diagnosis less than 50 year (OR 5.33 95% CI 1.27-22.33), age of first diagnosis 51-59 year (OR 4.07 95% CI 1.81-9.16), lunch without companion (OR 2.69 95% CI 1.25-5.82), daily lunch (OR 10.34 95% CI 2.02-53.9), polytherapy (OR 4.17 95% CI 1.95-8.90), difficulty in mobility (OR 2.12 95% CI 1.07-4.17) and amount of alcohol 2 glasses and more a week (OR 6.18 95% CI 1.84-20.77) were significantly contribute to the risk of poor glycaemic control after adjusting for potential covariates. Conclusions: Majority of the respondents had poor glycaemic control. Multiple lifestyle modifiable factors influenced the elderly type 2 diabetes. Therefore, there is a need to address these problems to the patients, their caregivers and the relevant party for an appropriate intervention to increase the awareness on selfmanagement and healthy living.